(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Lay deradicalisation and cybernetic literacy: the multisectorial strategy for the positive prevention of the new religious terrorism * ABSTRACT: Modern, religiously-motivated terrorism takes advantage of two newly emergent factors in order to attract new recruits: cognitive radicalization and cyberspace. The former consists of an entirely psychological process, one geared towards developing a religious-political system to subvert the democratic institutions of a country. The latter, on the other hand, is a tool which facilitates the continuous distribution of terrorist content online and the commission of new crimes, not prosecuted under the scope of criminal law’s traditional categories (cybercrimes). These two factors increase the probability that an aspiring terrorist will commit a crime the purposes of which are covered by the art. 270-sexies c.p. However, the Italian strategy to counteract this phenomenon remains focused on the hyperproduction of legal paradigms. Preventive measures adopted by the Italian legislator, on the other end, are exclusive negative and may not satisfy the requirements of the European Court of Human Rights in relation to the necessary guarantee of rights. Cybernetic literacy and deradicalisation are positive preventative measures, thus far unknown to the Italian legislator; their combined use negates the criminal potential of cognitive radicalisation and cyberspace usage through the stifling of the extreme political consequences, which arise when one professes a subversive religious strain developed by the cyber-radicalised. It is however, of the utmost importance that the principles of lay state and religious freedom are preserved when such measures are adopted. SOMMARIO: 1. Radicalizzazione e cibernetica: il nuovo volto del terrorismo religioso, la nuova sfida per gli ordinamenti giuridici occidentali - 2. La definizione penalmente rilevante di radicalizzazione religiosa - 3. Il cyberspazio come nuovo locus commissi delicti - 4. La reazione dell’ordinamento italiano al terrorismo religioso - 5. Profili critici connessi all’anticipazione della tutela penale in funzione preventiva - 6. Natura e contesto delle condotte con finalità di terrorismo (art. 270-sexies c.p.) - 7. Le misure di prevenzione negativa disciplinate dal d.lgs. 6 settembre 2011, n. 159 (così detto Codice antimafia): natura, funzione e rapporti con la pena in materia di contrasto al terrorismo - 8. I presupposti applicativi delle misure di prevenzione contro il terrorismo religioso alla luce della recente giurisprudenza della Corte europea dei diritti dell’uomo (la sentenza De Tommaso c. Italia e il parere consultivo 14 dicembre 2023) - 9. Gli indici della cyber-radicalizzazione quale forma di pericolosità terroristica - 10. Il modello di prevenzione positiva contro il terrorismo di matrice religiosa – 11. L’alfabetizzazione cibernetica nel contesto del cyberspazio - 12. La prevenzione positiva della deriva comportamentale del processo di radicalizzazione: la deradicalizzazione laica - 13. Osservazioni conclusive.